2006
DOI: 10.1007/s11373-005-9053-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimuscarinic actions of antihistamines on the heart

Abstract: SummaryAntimuscarinic side-effects, which include dry mouth, tachycardia, thickening of mucus possibly sedation, of the antihistamines limited the usefulness of these drugs. The advent of newer agents has reduced the sedative effect of the antihistamine. The data presented here show that one of the newest antihistamines, desloratadine, and a first generation drug, diphenhydramine, are both competitive inhibitors of muscarinic receptor mediated slowing of the heart as measured using a Langendorff preparation. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…Some histamine receptor antagonists are widely known to have anticholinergic effects but we found their activity at AsGAR-1 to be different to that at muscarinic receptors. Promethazine, an H1 receptor antagonist, diphenhydramine, an H1 antagonist, and cimetidine, an H2 antagonist, all display varying degrees of vertebrate muscarinic receptor antagonism (Kubo et al, 1987; Gwee and Cheah, 1990; 1991; Orzechowski et al, 2005; Liu et al, 2006). Only promethazine was an effective antagonist of AsGAR-1.…”
Section: Discussionmentioning
confidence: 99%
“…Some histamine receptor antagonists are widely known to have anticholinergic effects but we found their activity at AsGAR-1 to be different to that at muscarinic receptors. Promethazine, an H1 receptor antagonist, diphenhydramine, an H1 antagonist, and cimetidine, an H2 antagonist, all display varying degrees of vertebrate muscarinic receptor antagonism (Kubo et al, 1987; Gwee and Cheah, 1990; 1991; Orzechowski et al, 2005; Liu et al, 2006). Only promethazine was an effective antagonist of AsGAR-1.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, in general, was applied to classical antihistamines (for instance, chlorpheniramine and promethazine) that have been shown to inhibit muscarinic receptors (Brown and Eckberg, 1997;Yasuda and Yasuda, 1999;Shelton and McCarthy, 2000;Liu et al, 2006). However, recently developed "second-generation" antihistamines, such as astemizole and fexofenadine, also induce xerostomia (Wilson et al, 1987;Sreebny and Schwartz, 1997;Elad et al, 2006), despite their extremely low affinity for muscarinic receptors (Laduron et al, 1982;Liu et al, 2006). These observations suggest that xerostomia is not related solely to muscarinic receptor inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the xerostomia-inducing effect of antihistamines strongly suggests that histaminergic Ca 2Ï© signaling is functional in human salivary glands, there is no solid evidence for the expression of any histamine receptors. The current consensus is that antihistamine-induced xerostomia comes from an antimuscarinic effect; indeed, a number of studies have shown that first-generation histamine H1 receptor antagonists possess antimuscarinic activity (Yasuda and Yasuda, 1999;Liu et al, 2006).…”
mentioning
confidence: 99%
“…As evidĂȘncias indicam que a FEX Ă© segura e bem tolerada [44][45][46][47]50 , mesmo em doses atĂ© 11 vezes maiores do que as terapĂȘuticas 40 . É destituĂ­da de efeitos anticolinĂ©rgicos clinicamente significativos 51 .…”
Section: Fexofenadinaunclassified